2014
DOI: 10.1002/adma.201400561
|View full text |Cite
|
Sign up to set email alerts
|

Revelation of Intertwining Organic and Inorganic Fractal Structures in Polymer Coatings

Abstract: X-ray microtomography and serial block face scanning electron microscopy are used to reveal independent clusters of inorganic particles embedded within a polymer. These clusters are interpenetrating, of varying size, and have fractal dimensions that strongly influence transport and structure-property relations. This interpretation forms a baseline for designing hybrid materials for applications in self-healing, drug delivery, and membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 21 publications
(13 reference statements)
2
31
0
Order By: Relevance
“…This area has been covered in previous studies and will only be briefly addressed here [1,15] at room temperature. The sample was then allowed to dry prior to X-ray CT examination.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…This area has been covered in previous studies and will only be briefly addressed here [1,15] at room temperature. The sample was then allowed to dry prior to X-ray CT examination.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
“…Recently, the authors reported the presence of clusters of strontium chromate (SrCrO4) particles within an epoxy film which served as a model paint primer [1,2]. It was found that SrCrO4 particles formed intertwined clusters extending laterally in the plane of the film, the largest of which had fractal dimensions around 2.4.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Setup "Calcite clusters" display color as "One Colour per Data Value"; the channel display should resemble Figure 13(b). Details about clustering analysis and applications are published elsewhere [18][19][20] .…”
Section: Property Analysis and User Plug-in Developmentmentioning
confidence: 99%